Synopsis of the decisions of the Treasury Department on the construction of the tariff, navigation, and other laws : reformatted from the original and including, Synopsis of sundry decisions rendered by the Treasury Department, under tariff and other acts .
Vols. for 1891-1897 include decisions of the United States Board of General Appraisers.